The potential importance of the paternal contribution to the ‘Stock Reproductive Potential’ of North-East Arctic cod (Gadus morhua) - Nash, Richard D.M.; Kjesbu, Olav Sigurd; Thorsen, Anders; Fonn, Merete; Krüger-Johnsen, Maria; Trippel, Ed (ICES, 2005)
Over the years there has been a growing interest in determining the real stock reproductive potential (SRP) as a means of understanding the dynamics of a fish population. For the purposes of assessment the spawning stock biomass (SSB) is generally used, however, this is not a good descriptor for processes types of population modelling. In general, the focus in SRP studies has, with a few notable exceptions, been on female fecundity and realised egg production. In North-east Arctic cod, potential egg production for the stock, over the years 1946 to 2002 has been estimated. In this paper we present preliminary data on the total viable sperm production, estimated for the same years. There have been large changes in the total sperm production, which to a certain extent reflects changes in the mature biomass of the stock. Since 1946 there have also been changes in mean length of mature males and females with a tendency toward smaller fish in the most recent time period. With the relatively large decline in mean size of mature females and the tendency to mature at a smaller size in the latter years the mature fish of both sexes are now of a similar mean size. The relationship between mean size of mature males and females is substantially different than when the stock was large in the early part of the time series. This could have implications for fertilisation success, a factor that is dependent on the dynamics of both sexes.